Association between donor’s age and expression of cardiomyocyte marker quantity on adipocyte-derived mesenchymal stem cell - Bagus Fitriadi; Budi Baktijasa Dharmadjati; Mohammad Budiarto; Ryan Enast Intan; Firas Farisi Alkaff (Medicinski glasnik, 2022)
Aim: Adipocyte-derived mesenchymal stem cells (AMSCs) have recently been studied as a potential new approach for regeneration treatment of heart failure and ischemic myocardium. However, donor’s age is thought to affect the ability of AMSC cells to differentiate into cardiomyocytes. This study aimed to analyse the association between donor’s age with the expression of cardiomyocyte marker cardiac isoform of Troponin-T (cTnT) quantity on AMSCs. Methods: Subcutaneous adipose tissue was taken from donors of 3 different age groups (30-40, 41-50, and >50 years old), and then processed into AMSC cells by insert culture. AMSC cell phenotype was identified by assessing the quantity of mesenchymal markers expression (CD34, CD45, CD90, CD105) using indirect immunofluorescence technique. Afterwards, cTnT expression, a marker for cardiomyocyte differentiation from AMSC cells, was evaluated under the fluorescent microscope. The comparison was done between the 3 different age groups. Results: The comparative test and post hoc analysis showed that there were differences in the expression of CD34, CD45, CD90, CD105, and cTnT between the three age groups (all p<0.05). Furthermore, there were strong negative correlations between age and CD34, CD90, CD105 and cTnT (r= -0.844, -0.914, -0.899, and -0.738, respectively), while the correlation was positive between age and CD45 (r=0.899). Conclusion: Expression quantity of mesenchymal markers and cardiomyocyte markers from AMSC cells were affected by the donor’s age. The higher the donor age group, the lower the expression quantity of mesenchymal markers (except CD45) and cTnT.
Keywords: cardiomyocyte; donor; mesenchymal stem cells; troponin T